(untitled) (The Pakistan Development Review, 2003)
An agenda of economic reform encompassing a broad range of structural adjustment policies (SAP) is underway in Pakistan since 1987-88. These policies have an adverse impact on the pace of economic growth and created more poverty and inequality in the country [see Bengali and Ahmed (2002); Kemal (2003)]. These studies argues that during the last fifteen years each government is trying to stabilise the economy even at the cost of economic growth and delivery of social services. The negative impact of stabilisation policies on economic growth of the country is reflected in the decline of GDP growth from an average annual growth of 4.6 percent during 1990s as compared to 6.5 percent during 1980s. Similarly, negligence of social services delivery is reflected in the recent UNDP Report (2003), which, show that the ranking of Pakistan has slipped from 136 to 141 along with the decline in many other social sector statistics. The top government officials now also recognise these facts and the relapse of growth oriented policy can be heard more often. Trend in public finance statistics of the country clearly indicate that one of the important victim of stabilisation policies are the expenditures of provincial governments. In last several years the significant portion of onus of containment of fiscal deficit has been shifted towards the provincial governments. The onus of containment of fiscal deficit by all four provincial governments during the last decade has increased from 18 percent to 50 percent, which has devastating impact on the service provision and poverty reduction.